DICTION AND MORAL VALUES IN THE LAW OF THE SIMBUR CAHAYA OF CUSTOMARY CULTURAL LAW IN THE SOCIETY PERIOD OF PALEMBANG SULTANATE (PRAGMATIC SOCIOLINGUISTIC STUDIES) - Satria Wijaya; Sahid Teguh Widodo; Slamet Subiyantoro (Proceeding of International Conference on Art, Language, and Culture, 2017)
The aim of this research was to describe the diction and moral values in the Law of Simbur Cahaya of customary cultural law at the society period of the Sultanate of Palembang in Pragmatic Sociolinguistic study. The type of this research is literature study with qualitative descriptive method. Techniques of data collection using reading and writing techniques through content analysis approach. The results of this study are the category of moral values and characteristics of the use of diction in the Law of the Simbur Cahaya. The category of moral values, the moral values of human relationships with oneself, the moral value of human relationships with other human beings in the social sphere and the natural environment, and the moral value of human relationships with his Lord. While the characteristics of diction found, namely the diction of cultural society at the time of the Sultanate of Palembang which has a contextual meaning of local culture.